Optimized production of 89Zr as a medical radioisotope on a variable energy cyclotron and external beam-line - Diana Cocioabă; Simona Baruta; Liviu Crăciun; Radu Leonte; Andrei Necsoiu; Maria-Roxana Tudoroiu-Cornoiu; Alexandru Jipa; Dana Niculae (EJNMMI Physics)
Abstract Background Zirconium-89 (89Zr) is a highly valued diagnostic radionuclide for positron emission tomography (PET) due to its long physical half-life of 78.4 h and decay characteristics, being preferred for the radiolabelling of nanoparticles and slow kinetics macromolecules, such as antibodies. 89Zr-based high-resolution PET images can be employed to scan tumours and localize the tracer on a longer timeframe, which allows for real-time therapy monitoring. The goal of this study was to maximize the 89Zr production yield by fine-tunning the irradiation parameters of a solid target, in two different experimental set-ups, using a variable energy 14–19 MeV TR-19 cyclotron. Monte Carlo programs simulated the irradiation geometry and estimated the activity and irradiation yields produced by the 89Y(p, n)89Zr reaction, at the process optimal parameters. The resulted data were compared with the experimental data collected in our particular irradiation setups. Results 89Zr was obtained from natY foil target using: (A) the solid target holder placed on the extraction port, and (B) the automated solid target irradiation station, installed on a sloped-down extension of the proton beamline. The two irradiation geometries are differentiated by the distances from the respective extraction ports, beam-geometry and shape, cooling capacity, and degrader’s thickness. Based on the specific geometries, A and B, the Monte Carlo simulations output determined the optimal experimental irradiation parameters (extracted energy, degrader thickness, proton current intensity), as well as the target thickness. The 250 μm natY foils were irradiated with 14 MeV protons and an integrated current of 32 µA·h, on the solid target configuration A, and with 15.2 MeV protons, 100 µA·h on the solid target configuration B. After the dissolution and purification of the targets, [89Zr]Zr-oxalate solutions of 1.28 ± 0.18 GBq, and 2.95 ± 0.31 GBq respectively, were evaluated, to determine the radionuclidic purity and contaminant levels of 89Zr solutions across different incident proton beam energies. The pharmaceutical specifications require the solutions radionuclidic purity to be above 99.9% of the total radioactivity, as criteria of their suitability for use as radiopharmaceutical precursors for antibodies radiolabelling. Conclusions Simulations were providing optimized input parameters to maximize the production yield of 89Zr and subsequently, to achieve the highest possible activity with no detriment to radionuclide purity, as per the [89Zr]Zr-oxalate solution pharmaceutical specification. The parameters were then implemented in the experiments, and the production processes were tested on two particular irradiation configurations. The yields and activities produced through 89Y(p, n)89Zr reaction, at the TR-19 cyclotron were in good agreement with the simulations, within 18.4–21.3%, which include activity losses during irradiation and post-processing and uncertainties resulted from activity measurements and cross-section values.